Digital Transformation and Appropriate Technology Application to Improve the Competitiveness of Singosari Batik - Nurfa Anisa; Mohammad Dullah; Juli Rahaju; Eny Dyah Yuniwati (Pascasarjana Universitas Mataram, 2025)
This community service program strengthens the competitiveness of the Singosari Batik Association through digital transformation and appropriate technology. The association consists of around 30 artisans, mostly women, but faces constraints in wastewater management, limited use of natural dyes, and weak digital marketing. Using a descriptive qualitative approach with participatory action research, the program applied participatory observation, in-depth interviews, focus group discussions, and documentation of production, waste management, and marketing activities. Interventions were designed and implemented in three areas: RO+ wastewater treatment technology, plant-based natural dye technology, and digital marketing for batik promotion and sales. The RO+ system combines multistage pretreatment, sedimentation, and reverse osmosis to reduce pollutant loads in batik wastewater before discharge. Natural dye training introduced plant-based dye sources, extraction and dyeing techniques, and fixation using ferrous sulfate (tunjung) to improve color fastness. Digital marketing interventions included training on content creation, branding, social media management, marketplace use, and TikTok Live–based selling. The results show increased awareness and capacity for environmentally friendly production, supported by RO+ technology and standard operating procedures for wastewater management. The adoption of natural dyes expanded product variety and strengthened the identity of “environmentally friendly Singosari batik.